The effectiveness of Artificial Intelligence (AI) in learning outcomes of nursing students : A meta-analysis of randomized controlled trials (RCTs) - Jandy Perra, Jembu; Shalin Wan Fei, Lee (American Institute of Mathematical Sciences, 2025)
Background Artificial intelligence (AI) has the potential to revolutionize nursing education by enhancing learning experiences and educational outcomes. While researchers have investigated the usefulness of AI-based technology in nursing education, a systematic review emphasising randomised controlled trials (RCTs) is required to provide solid evidence to address educators' scepticism of its application. In this review, we provide evidence-based insights from RCTs to guide nursing educators and policymakers in enhancing educational practices.